Pengaruh Work From Home dan Lingkungan Kerja terhadap Produktivitas Kerja pada masa Pandemi covid-19 (Studi pada Guru SMPN 12 Kota Malang) - Anisya Nurisnaini Safitri; Nurhajati Nurhajati; M. Ridwan Basalama (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractIn recent months the world has been in shock with the deadly corona virus or Covid-19. This has caused a number of aspects of people's lives to be affected because of this corona virus and has made teachers have to be able to adapt to the new work system.  This study aims to determine the effect of Work From Home and Work Environment on Work Productivity at SMPN 12 Malang City Teachers. The population in this study amounted to 40 employees with a saturated sampling technique, where all members of the population were sampled.  Using multiple linear regression analysis, and the results of the study show that Work From Home and Work Environment have a simultaneous influence on Teacher Work Productivity at SMPN 12 Malang Work From Home has no partial effect on teacher work productivity at SMPN 12 Malang and the Work Environment has a partial effect on  Teacher work productivity at SMPN 12 Malang